PEG-induced osmotic stress in Mentha x piperita L.: Structural features and metabolic responses - Búfalo, Jennifer [UNESP]; Rodrigues, Tatiane Maria [UNESP]; de Almeida, Luiz Fernando Rolim [UNESP]; Tozin, Luiz Ricardo dos Santos [UNESP]; Marques, Marcia Ortiz Mayo; Boaro, Carmen Silvia Fernandes [UNESP] (Elsevier, 2016)
The present study investigated whether osmotic stress induced by the exposure of peppermint (Mentha x piperita L.) to moderate and severe stress for short periods of time changes the plant's physiological parameters, leaf anatomy and ultrastructure and essential oil. Plants were exposed to two levels of polyethyleneglycol (50 g L-1 and 100 g L-1 of PEG) in a hydroponic experiment. The plants exposed to 50 g L-1 maintained metabolic functions similar to those of the control group (0 g L-1) without changes in gas exchange or structural characteristics. The increase in antioxidant enzyme activity reduced the presence of free radicals and protected membranes, including chloroplasts and mitochondria. In contrast, the osmotic stress caused by 100 g L-1 of PEG inhibited leaf gas exchange, reduced the essential oil content and changed the oil composition, including a decrease in menthone and an increase in menthofuran. These plants also showed an increase in peroxidase activity, but this increase was not sufficient to decrease the lipid peroxidation level responsible for damaging the membranes of organelles. Morphological changes were correlated with the evaluated physiological features: plants exposed to 100 g L-1 of PEG showed areas with collapsed cells, increases in mesophyll thickness and the area of the intercellular space, cuticle shrinkage, morphological changes in plastids, and lysis of mitochondria. In summary, our results revealed that PEG-induced osmotic stress in M. x piperita depends on the intensity level of the osmotic stress applied; severe osmotic stress changed the structural characteristics, caused damage at the cellular level, and reduced the essential oil content and quality.
Keywords: Antioxidant enzymes; Essential oils; Hydroponics; Leaf ultrastructure; Mint; Polyethyleneglycol; Water deficit